Preservation of Biochemical Liver Function With Low-Dose Soy-Based Lipids in Children With Intestinal Failure–Associated Liver Disease. Issue 3 (March 2015) - Khan, Faraz A.; Fisher, Jeremy G.; Sparks, Eric A.; Potemkin, Alexis; Duggan, Christopher; Raphael, Bram P.; Modi, Biren P.; Jaksic, Tom
ABSTRACT: Objectives: Intestinal failure–associated liver disease (IFALD) contributes to significant morbidity in pediatric patients with intestinal failure (IF); however, the use of parenteral nutrition (PN) with a fish oil–based intravenous (IV) emulsion (FO) has been associated with biochemical reversal of cholestasis and improved outcomes. Unfortunately, FO increases the complexity of care: because it can be administered only under Food and Drug Administration compassionate use protocols requiring special monitoring, it is not available as a 3-in-1 solution and is more expensive than comparable soy-based IV lipid emulsion (SO). Because of these pragmatic constraints, a series of patient families were switched to low-dose (1 g kg −1  day −1 ) SO following biochemical resolution of cholestasis. The present study examines whether reversal of cholestasis and somatic growth are maintained following this transition. Methods: The present study is a chart review of all children with IFALD who switched from FO to SO following resolution of cholestasis. Variables are presented as medians (interquartile ranges). Comparisons were performed using the Wilcoxon signed-rank test. Results: Seven patients ages 25.9 (16.2–43.2) months were transitioned to SO following reversal of cholestasis using FO. At a median follow-up of 13.9 (4.3–50.1) months, there were no significant differences between pretransition and post-transition serum alanine and aspartate aminotransferases, direct bilirubin, and weight-for-age z scores. Because of recurrence of cholestasis, 1 patient was restarted on FO after 4 months on SO. Conclusions: Biochemical reversal of IFALD and growth were preserved after transition from FO to SO in 6 of 7 (86%) patients. Given the challenges associated with the use of FO, SO may be a viable alternative in select patients with home PN.